Applied artificial intelligence: acceptance-intention-purchase and satisfaction on smartwatch usage in a Ghanaian context - Uzir, Md Uzir Hossain; Bukari, Zakari; Al Halbusi, Hussam; Lim, Rodney; Wahab, Siti Norida; Rasul, Tareq; Thurasamy, Ramayah; Jerin, Ishraq; Chowdhury, M Rezaul Karim; Tarofder, Arun Kumar; Yaakop, Azizul Yadi; Abdul Hamid, Abu Bakar; et al. (Elsevier Ltd., 2023)
Technology and its continuous advancement facilitate human beings to get rid of their criticality and limitation. Applied artificial intelligence (AAI) is one of the latest forms that delimited the limitation of human beings. Smartwatch acts as an applied artificial intelligence to assist various patients to check medical care without going to hospital and physicians. This (three) multiplestudy research focused on the intention to use, purchase, and their satisfaction and spread positive word of mouth among others in the Ghanaian. To investigate these issues two renowned theories were underpinned- TAM theory and the Stimulus-Organism-Response (S–O-R). Total 550, 320, and 170 respondents were interviewed with Google forms due to COVID-19 using social media. AI-enabled smartwatch considering Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Perceived Credibility (PC), Perceived Self-Efficacy (PSE), and Perceived Financial Cost (PFC) were significant on intention to adoption and adoption intention on actual purchase. The final study showed device quality, its service level, their usage experience, perceived value, and the extent to which the satisfied customers made positive word of mouth to their friends and family, colleagues and followers. This research is significant in understanding the usage of AIenabled smartwatches as a device doctor or electronic doctor (e-doctor).